GamblingLess: Curb Your Urge: Development and usability testing of a smartphone-delivered ecological momentary intervention for problem gambling. Issue 3 (1st September 2020) - Merkouris, Stephanie S.; Hawker, Chloe O.; Rodda, Simone N.; Youssef, George J.; Dowling, Nicki A.
ABSTRACT: Smartphone apps are suitable for delivering mental health treatment in real-time. This study aimed to develop and test the usability of one of the first smartphone app-delivered ecological momentary interventions for gambling (GamblingLess: Curb Your Urge ), with key Australian stakeholders (ten consumers, nine gambling clinicians, and ten gambling researchers). Based on relapse prevention principles, the intervention comprised 10 activities to curb cravings, which were recommended to participants based on ecological momentary assessments (EMAs) of gambling cravings. Participants tested the usability of the intervention over one-week and reported on the content's helpfulness, the EMA's relevance/burden, the Mobile App Rating Scale, and open-ended items assessing content and functionality. The intervention content, helpfulness, and usability were rated highly in quantitative and qualitative assessments. Participants liked practical and instructive content, but suggested that the intervention could be more engaging, interactive, and varied, and the number of EMA questions per timepoint could be reduced. These preliminary findings were promising for the intervention's acceptability and usability. All groups indicated that they would recommend this app, as it could increase knowledge, attitudes, awareness, behavior change, intention to change, and help-seeking for gambling cravings. Further research is required to refine the intervention and examine its effectiveness with gamblers.